2016
DOI: 10.1098/rsta.2015.0318
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional inorganic analogues of graphene: transition metal dichalcogenides

Abstract: The discovery of graphene marks a major event in the physics and chemistry of materials. The amazing properties of this two-dimensional (2D) material have prompted research on other 2D layered materials, of which layered transition metal dichalcogenides (TMDCs) are important members. Single-layer and few-layer TMDCs have been synthesized and characterized. They possess a wide range of properties many of which have not been known hitherto. A typical example of such materials is MoS 2 . In this article, we brief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 183 publications
(325 reference statements)
4
46
0
Order By: Relevance
“…Mallouk et al [79] confirmed that the peaks of E g can switch between 284 and 307 cm −1 . Furthermore, other reports clarified that the J 1 , J 2 , and J 3 can also shift a little, [65,66,80,81] which is probably due to the different layer distance. Generally, Raman spectra measurement is the most basic technique to identify the metallic phase of MoS 2 .…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Mallouk et al [79] confirmed that the peaks of E g can switch between 284 and 307 cm −1 . Furthermore, other reports clarified that the J 1 , J 2 , and J 3 can also shift a little, [65,66,80,81] which is probably due to the different layer distance. Generally, Raman spectra measurement is the most basic technique to identify the metallic phase of MoS 2 .…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…The outstanding properties of graphene and related 2D materials (GRM) have been attracting great attention and they are being explored to create nanomaterials that perform multiple functions in various applications. [1][2][3][4][5][6][7][8][9][10][11][12][13] Composites are the most common industrial graphene-based products but the quality of commercially available graphene is usually low, compared to the materials obtained in the laboratory. Graphene is often commercially supplied as a powder and it is not possible to expect that <1 nm thin, electroneutral sheets will remain well separated, when they touch each other, due to the omnipresent van der Waals forces.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis is one of the environmental-friendly methods to degrade organic pollutants, reduce carbon dioxide and realize solar energy conversion. [1][2][3][4][5][6] Among the semiconductor materials, two-dimensional (2D) transition-metal dichalcogenides (TMDs), such as MoS 2 , have attracted numerous attention owing to their unique photoelectric properties, [7][8][9][10] especially for the utilization in catalysis. Indeed, 2HÀ MoS 2 is an ideal photocatalytic material with band gap value around 1.2~1.9 eV, [11] showing superior catalytic ability at the edge of 2D structure.…”
Section: Introductionmentioning
confidence: 99%